Law No. 5 of the Year 2018 on Amending some Provisions of the Penal Code Promulgated by Law No. 58 of the Year 1937 = قانون رقم 5 لسنة 2018 بتعديل بعض أحكام قانون العقوبات الصادر بالقانون رقم 58 لسنة 1937 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic